Loading web-font TeX/Math/Italic

5.9(x+2)=3(x-2)x=

Simple and best practice solution for 5.9(x+2)=3(x-2)x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.9(x+2)=3(x-2)x= equation:



5.9(x+2)=3(x-2)x=
We move all terms to the left:
5.9(x+2)-(3(x-2)x)=0
We multiply parentheses
5.9x-(3(x-2)x)+11.8=0
We calculate terms in parentheses: -(3(x-2)x), so:
3(x-2)x
We multiply parentheses
3x^2-6x
Back to the equation:
-(3x^2-6x)
We get rid of parentheses
-3x^2+5.9x+6x+11.8=0
We add all the numbers together, and all the variables
-3x^2+11.9x+11.8=0
a = -3; b = 11.9; c = +11.8;
Δ = b2-4ac
Δ = 11.92-4·(-3)·11.8
Δ = 283.21
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
x_{1}=\frac{-b-\sqrt{\Delta}}{2a}
x_{2}=\frac{-b+\sqrt{\Delta}}{2a}

x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(11.9)-\sqrt{283.21}}{2*-3}=\frac{-11.9-\sqrt{283.21}}{-6}
x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(11.9)+\sqrt{283.21}}{2*-3}=\frac{-11.9+\sqrt{283.21}}{-6}

See similar equations:

| 4.6x-8+2x-5=7-2xx= | | 3.5x+2=x-6x= | | 7x-5(3x-15)=19 | | 2.5x+3=2x+15x= | | 3x+4x-6=15 | | 3(y+2)=2(2y-7)+y | | 8x-1=-4x+23x= | | 8n+12-5=21 | | 3-3=1-r | | 3+3=1+-r | | x+x+55=90 | | (8x+16)=(5x+40) | | 4/5x-3=2(5+1/3x) | | 6-4d=9-13d | | 0.03x2=0 | | -13.1=y/6+6.1 | | 13x2+1.69=0 | | 5x-2(4x+1)=1 | | 0.3x+10=5.2x-19 | | x=4+1/4 | | -2x-6=8x-6 | | 4x+4=2(2-1) | | 2x+20=6.5 | | 3=r-r+1 | | x2-1.44=0 | | 5x-22+2x=5x-22 | | -9(n+4)=5n-(4n+36) | | 8x=140+x | | 1/4(25x+3/5)=2.5-3/8x | | (2/3)(9c-3)=22 | | 2/9x=0.66 | | 1/9x2-2=0 |

Equations solver categories